Patients' Characteristics and Environmental Factors Affecting Skin Cancer Detection: A Multicentre Prospective Study - Álvaro Iglesias-Puzas; Alberto Conde-Taboada; Beatriz Aranegui-Arteaga; Lucía Campos-Muñoz; Eduardo López-Bran (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)